Anion texturing towards dendrite-free Zn anode for aqueous rechargeable battery - Yuan, Du (2021)
The reversibility of metal anode is a fundamental challenge to the lifetime of rechargeable batteries. Though being widely employed in aqueous energy storage systems, metallic zinc suffers from dendrite formation that severely hinders its applications. Here we report texturing Zn as an effective way to address the issue of zinc dendrite. An in‐plane oriented Zn texture with preferentially exposed (002) basal plane is demonstrated via a sulfonate anion‐induced electrodeposition, noting no solid report on (002) textured Zn till now. Anion‐induced reconstruction of zinc coordination is revealed to be responsible for the texture formation. Benchmarking against its (101) textured‐counterpart by the conventional sulphate‐based electrolyte, the Zn (002) texture enables highly reversible stripping/plating at a high current density of 10 mA cm−2, showing its dendrite‐free characteristics. The Zn (002) texture‐based aqueous zinc battery exhibits excellent cycling stability. The developed anion texturing approach provides a pathway towards exploring zinc chemistry and prospering aqueous rechargeable batteries.